Phenotype expansion, or double trouble: the combination of congenital disorder of glycosylation type 1i and Joubert syndrome type 17 - M. V. Sharova; T. V. Markova; A. L. Chukhrova; O. A. Shchagina; E. L. Dadali (Нервно-мышечные болезни)
The co-occurrence of two genetic disorders in a single patient, so called double trouble phenomenon, is a rare clinical scenario that significantly complicates the diagnostic process. This is particularly challenging when both disorders affect the nervous system, leading to overlapping phenotypes. Congenital disorders of glycosylation, including the rare congenital 1i type caused by variants in the ALG2 gene, are characterized by psychomotor delay, microcephaly, seizures, hepatomegaly, and ophthalmological abnormalities. Joubert syndrome, associated with variants in the CPLANE1 gene, presents with brain malformations, severe psychomotor delay, oculomotor apraxia, and respiratory disturbances. In this study, we describe a patient with a rare combination of congenital disorders of glycosylation 1i type and Joubert syndrome type 17, caused by previously unreported variants in the ALG2 and CPLANE1 genes. This case highlights the diagnostic challenges and the need for a comprehensive approach in managing patients with multiple genetic disorders.